1978
DOI: 10.1136/ard.37.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosing spondylitis and inflammatory bowel disease. III. Clinical characteristics and results of histocompatibility typing (HLA B27) in 50 patients with both ankylosing spondylitis and inflammatory bowel disease.

Abstract: SUMMARY A study was made, in co-operation with several gastroenterology and rheumatology centres, of the clinical and genetic characteristics (HLA B27) of 50 patients suffering from both inflammatory bowel disease (38 Crohn's disease (CD), 12 ulcerated colitis (UC)) and ankylosing spondylitis (AS), the latter diagnosis being established according to the New York criteria. 20 CD (52 -6 %O) and 8 UC (66 * 7 %) patients were HLA B27 positive. The presence of HLA B27 was studied in relation to clinical parameters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
7

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 36 publications
3
9
0
7
Order By: Relevance
“…This is perhaps best illustrated by the recent studies on arthritis in IBD. Despite similarities to other HLA-B27 related diseases no HLA association had been demonstrated with peripheral arthritis in IBD [23,52]. However clinical analysis of the patterns of disease led to the subdivision of arthritis into Type 1 (a large joint acute arthritis) and Type 2 (a small joint chronic polyarthritis) [53].…”
Section: Phenotypic Considerationsmentioning
confidence: 99%
“…This is perhaps best illustrated by the recent studies on arthritis in IBD. Despite similarities to other HLA-B27 related diseases no HLA association had been demonstrated with peripheral arthritis in IBD [23,52]. However clinical analysis of the patterns of disease led to the subdivision of arthritis into Type 1 (a large joint acute arthritis) and Type 2 (a small joint chronic polyarthritis) [53].…”
Section: Phenotypic Considerationsmentioning
confidence: 99%
“…The intestinal disease-arthritis association is particularly strong in patients with IBD. Early work showed that 10-18% of patients with classic IBD develop sacroiliitis (8), with features that differ from those of idiopathic AS only in that the prevalence of HLA-B27, while still high in IBD-associated sacroiliitis, is significantly lower than in idiopathic AS (9). These HLA-B27 associations are thought to be very important.…”
Section: Enteric Arthritis or Arthritic Enteritis?mentioning
confidence: 99%
“…So leiden HLA-B27-positive Patienten mit chronisch entzª Darmerkrankungen zu 50 bis 90% an einem Befall des Achsenskeletts [21]. 2) den mit HLA-Klasse-I-Antigenen sind fª periphere Arthritiden mit dem HLA-B17 [18], fª klinisch blande Verltiufe mit dem HLA-B62 [16] und in einer grol3en deutschen Studie mit dem HLA-B44 [20] beschrieben. Weitete Assoziationen von enteropathischen Spondarthriti-colopr(x:to[ogy 19 (1997), 59~,6 (Nr.…”
Section: Diskussionunclassified